Cell recruitment and the origins of Anterior-Posterior asymmetries in the Drosophila wing - Rosalío Reyes; Rafael Rodriguez-Muñoz; Marcos Nahmad (PLoS ONE, 2025)
The mechanisms underlying the establishment of asymmetric structures during development remain elusive. The wing of Drosophila is asymmetric along the Anterior-Posterior (AP) axis, but the developmental origins of this asymmetry is unknown. Here, we investigate the contribution of cell recruitment, a process that drives cell fate differentiation in the Drosophila wing disc, to the asymmetric shape and pattern of the adult wing. Genetic impairment of cell recruitment in the wing disc results in a significant gain of AP symmetry, which results from a reduction of the region between longitudinal vein 5 and the wing margin (L5-M) in the adult wing. Morphometric analysis confirms that blocking of cell recruitment results in a more symmetric wing with respect to controls, suggesting a contribution of cell recruitment to the establishment of asymmetry in the adult wing. In order to verify if this phenotype is originated during the time in which cell recruitment occurs during larval development, we examined the expression of a reporter for the selector gene vestigial (vg) in the corresponding pro-vein regions of the wing disc, but our findings could not explain our findings in adult wings. However, the circularity of the Vg pattern significantly increases in recruitment-impaired wing discs, suggesting that cell recruitment may contribute to AP asymmetries in the adult wing shape by altering the roundness of the Vg pattern. We conclude that cell recruitment, a widespread mechanism that participates in growth and patterning of several developing systems, may contribute, at least partially, to the asymmetric shape of the Drosophila wing.